2013
DOI: 10.3744/snak.2013.50.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Density Ratio of Gas and Liquid in Sloshing Experiment

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License(http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. This paper presents the results of sloshing experiments having different fluids in model tanks with various density ratios. The experimental model consisting water and air at ambient, which has been commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…From sloshing model tests performed with water and different ullage gases or vapor (Maillard and Brosset (2009), Ahn et al (2012)), it has been shown that, statistically and for all level of probability to be considered, the heavier the ullage gas, the smaller the pressures. Based on this result, sloshing model tests for any project of LNG floating tank are now performed with a heavy gas made of a mixture of SF 6 and N 2 tuned in order to match the DR in real LNG tanks (close to 0.004).…”
Section: Contextmentioning
confidence: 99%
“…From sloshing model tests performed with water and different ullage gases or vapor (Maillard and Brosset (2009), Ahn et al (2012)), it has been shown that, statistically and for all level of probability to be considered, the heavier the ullage gas, the smaller the pressures. Based on this result, sloshing model tests for any project of LNG floating tank are now performed with a heavy gas made of a mixture of SF 6 and N 2 tuned in order to match the DR in real LNG tanks (close to 0.004).…”
Section: Contextmentioning
confidence: 99%
“…Because the same liquid and gas were used for both the conventional and the modified tank, the influence of the density ratio was not relevant. There are several studies on the influence of liquid-gas density ratio in sloshing [14,15].…”
Section: Model Test Setupmentioning
confidence: 99%
“…12 Furthermore, either short-term or long-term model test is suggested, according to our experiment, the recommended minimum time for model test seems significantly lower than the time for convergent pressure prediction. [13][14][15][16] This paper introduces an outlier analysis method, which can improve the convergence through the statistical analysis of experimental values lacking convergence, and is based on the doctoral thesis of Kim 17 and also extending the study of Kim and Kim. 18 In this study, a new method is proposed to detect and treat anomalies in the sloshing model experiment data.…”
Section: Introductionmentioning
confidence: 99%